1965
DOI: 10.1146/annurev.pa.05.040165.000331
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Metabolism of Chlorinated Hydrocarbon Insecticides Especially in Mammals

Abstract: This review discusses the absorption, storage, biotransformation, and excretion of chlorinated hydrocarbon insecticides; thus, it emphasizes those aspects of physiology that can be studied by the methods of analytical or ganic chemistry. The broader aspects of toxicity, as they relate to the me tabolism of these materials, were discussed by Winteringham & Barnes (1).This review emphasizes mammalian metabolism of the compounds, but con tains some information on their metaboli sm by other organisms, a subject th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 63 publications
0
25
0
1
Order By: Relevance
“…The increase in the triglyceride content in the liver might also increase the content of PECB in the tissue. It is reported that tissue lipids contents, especially triglyceride, influence the accumulation of DDT and dieldrin in the tissue (16).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the triglyceride content in the liver might also increase the content of PECB in the tissue. It is reported that tissue lipids contents, especially triglyceride, influence the accumulation of DDT and dieldrin in the tissue (16).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of DDT in several animal species has been reviewed by Hayes (1959Hayes ( , 1965, O'Brien more a result of storage of pp'DDE present in food. This (and the fact that residues in animal carcasses are based on total DDT content) means that the increase in, and the persistence of.…”
Section: Discussionmentioning
confidence: 99%
“…No significant gender difference was observed in this study. In the rat, several studies indicate that faecal excretion of DDT and p, (Hayes, 1965). Bishara and co-workers (1972) reported that of a 10 mg dose of p,p'-DDT orally given to rats, 2.6 % was excreted in urine and 59.4 % in faeces in 5 days.…”
Section: Excretionmentioning
confidence: 99%